A supramolecular silicone dielectric elastomer with a high dielectric constant and fast and highly efficient self-healing under mild conditions. Issue 44 (9th November 2020) - Sun, Haibin; Liu, Xueying; Liu, Suting; Yu, Bing; Ning, Nanying; Tian, Ming; Zhang, Liqun
Abstract : A silicone dielectric elastomer with simultaneous high dielectric constant, fast and efficient self-healing ability at mild conditions was prepared by constructing supramolecular network assembled by coordination bonds and hydrogen bonds. Abstract : Dielectric elastomer (DE) materials suffer from high driving voltages and cracks or breaks during repetitive actuation cycles. New DE materials with a simultaneous high dielectric constant ( ε ′) and fast and efficient self-healing ability are in urgent need. Herein, we report a self-healable silicone DE by constructing a supramolecular network assembled by coordination bonds between carboxylated polymethylvinylsiloxane (PMVS-COOH) and FeCl3 as well as hydrogen bonds between carboxyl groups through introducing FeCl3 into PMVS-COOH. Both experimental results and density functional theory indicate that the Fe 3+ /COO − complex is formed and can further aggregate into clusters, which can simultaneously realize the crosslinking of PMVS-COOH and introduce interfacial polarization. Interestingly, the interfacial polarization largely increases with increasing FeCl3 content and FeCl3 can promote dipole polarization by disrupting some of the hydrogen bonds and releasing carboxyl groups when the FeCl3 content is higher than 5%, leading to a significant enhancement in ε ′. The as-prepared PMVS-COOH/FeCl3 (SiR-Fe) DE with 8% FeCl3 shows comparatively high ε ′ (12.3 at 10 4 Hz), much higher than that of the commercial silicone DE (∼2.7) or PMVS-COOH (6.1). Meanwhile, a self-healing efficiency of 99% in tensile strength and 100% in tensile toughness are achieved for SiR-Fe with 8% FeCl3 after being treated for 1 h at room temperature. This is ascribed to the high chain mobility of SiR-Fe and the robust supramolecular dynamic network resulting from the combination of coordination bonds and hydrogen bonds. It is demonstrated that SiR-Fe can be effectively used as a dielectric elastomer sensor. And it is promising that this highly efficient self-healable SiR-Fe DE with high ε ′ finds applications especially in biological and medical fields.